- Constructional Growth Trends and its Impact on Religious Archaeological Areas in AL- Madinah Al Munawarah - Geographical study - Al - Balaa, Haifa Yahya (Journal of natural sciences, life and applied sciences, 2018)
The study examined the Trends in urban crawling and its impact on religious archeological sites in Madinah El Munawarah and the knowledge of the urban extension between the period (1990-2014)، during a period of time 24 years، As well as the impact of this urban expansion and skyscraper on the areas of religious relics in Medina and the uses of land in in Madinah El Munawarah.The study was based on the Descriptive method، and going for field visits، analysis and evaluation approach and carried For tourist archaeological sites، The most important of which is the spatial analysis approach، who is interested in highlighting disparities، and similarities. For the distribution of spatial phenomenon and the inductive method. To monitor the state of the geographical reality of the phenomenon studied. The historical approach، Regional approach، and use of GIS and remote sensing، and The study reached the direction of urbanization towards the eastern and western sides، As a result of urban encroachment، it led to the fusion of archaeological and religious sites in AL-Madinah al Munawarah In the areas of urban such as The area of Shohadaa Ohod، Algoma Mosque، and Seven Mosques، and all famous religion.
Keywords: archaeological tourism; population growth; urban sprawl; central region